2009
DOI: 10.1088/0268-1242/24/10/105024
|View full text |Cite
|
Sign up to set email alerts
|

Studies of mist deposition for the formation of quantum dot CdSe films

Abstract: Films of CdSe(ZnS) colloidal nanocrystalline quantum dots (NQDs) were deposited on bare silicon, glass and polymer coated silicon using mist deposition. This effort is a part of an exploratory investigation in which this deposition technique is studied for the first time as a method to form semiconductor NQD films. The process parameters, including deposition time, solution concentration and electric field, were varied to change the thickness of the deposited film. Blanket films and films deposited through a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…19 New SnO 2 and F:SnO 2 precursors are needed to take advantage of spin processing for advanced thin-film applications. Such new precursors would also be useful for other, related, lowtemperature solution-deposition processes including mist, 26 dip, 27 slot-die, 28 or capillary 29,30 deposition and thus further enable the large-area or roll-to-roll deposition of functional inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…19 New SnO 2 and F:SnO 2 precursors are needed to take advantage of spin processing for advanced thin-film applications. Such new precursors would also be useful for other, related, lowtemperature solution-deposition processes including mist, 26 dip, 27 slot-die, 28 or capillary 29,30 deposition and thus further enable the large-area or roll-to-roll deposition of functional inorganic materials.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these nanocrystals are capped with organic ligands that make them dispersible in aqueous/organic solutions. Therefore, they can be integrated easily into the conventional organic LEDs (OLEDs) with the use of common low-cost techniques such as spin-coating, , dip-coating, layer-by-layer assembly, , inkjet printing, contact printing, and mist deposition . The hybrid combination of organic semiconductors and inorganic nanocrystal colloids potentially allows for new possibilities to control exciton formation, hence achieving high light-emission efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the mist deposition process can create patterns on the substrate surface and that it is possible to pattern separate coloured CdSe/ZnS core/shell QDs (purchased from Ocean Nano Tech) without damaging any previously deposited QD layer [10,11]. The ability to replicate a pattern accu− rately will prove necessary when patterning three separate colours closely together.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to replicate a pattern accu− rately will prove necessary when patterning three separate colours closely together. Mist deposition can be used to cre− ate patterned depositions of multiple colours in the micron range without damage to other existing layers [10,11]. The mist deposition process has been used for other LED appli− cations already such as blue OLED technology, and proven its ability to create high brightness LEDs [12].…”
Section: Introductionmentioning
confidence: 99%